Response of spatial and temporal variations of ecosystem service value to land use/land cover transformation in the upper basin of Miyun Reservoir - Ziheng Feng; Liying Sun (Ecological Indicators, 2024)
Understanding the spatial and temporal differentiation of ecosystem service value (ESV) brought about by land use/land cover (LULC) transformation is of significance to the ecosystem management policy making and decision supports. In this research, the upper basin of Miyun Reservoir in northern Beijing was chosen as study area because of its importance to ecological security of Beijing, the Capital City of China. The equivalent factor method was used to evaluate the ESV, and the responses of spatial and temporal variations of ESV to LULC transformations were explored by gridding and spatial autocorrelation analysis during years 1990–2020. The results indicate that the total ESV increase from 19.367 billion Yuan to 20.419 billion Yuan during 1990–2020. Forest is the most significant LULC type to ESV, contributing over 85% to the total ESV each year and contributing more than 50% to the changes of ESV. The continuous transformation of grassland, cropland and shrub to forest is the main reason for the increase in total ESV in the study area. The geographical distribution of LULC directly influences the spatial distribution characteristics of ESV, resulting in a strong spatial positive autocorrelation of ESV. The spatial and temporal variations of LULC and ESV around Miyun Reservoir reflect the significant conflict between human activities and ecological protection. The recommendation is to limit the expansion of construction land and cropland with high efficiency and to expand forest and water to continuously increase ESV. This study provides support for land use planning, ecological health and environmental protection in the upper basin of Miyun Reservoir in Beijing, as well as methodological references for exploration in hilly areas facing the conflict between economic development and ecological protection.